Engaging in creative teaching pedagogy based on slstat gamification for learning statistics / Norbaiti Tukiman ... [et al.] - Tukiman, Norbaiti; Foong, Ng Set; Khalid, Ahmad Khudzairi; Ahmad, Nur Intan Syafinaz; Mohamed, Suhana (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Learning pedagogy and strategy is important to enhance students' interest in the critical subjects or topics. Statistics is one of the subjects studied by UiTM students pursuing a Diploma in Business Transport. An innovative board game called Snake and Ladder for Fun Statistical Learning has been created in order to solve problem in learning probability (the concept in statistical learning). In this study, the traditional board game Snake and Ladder was modified by incorporating the element of learning into the newly created games namely SLSTAT. The games applied to students who took the course. Qualitative method through interview questionnaires has been used to analyse the students' interest of SLSTAT game towards the probability topic and student engagement SLSTAT game in their learning outcome. The outcomes of this game are as follows: (1) Students can apply probability, and (2) they can collaborate to solve probability-related problems. The results show most of students are likely agree that SLSTAT assist their understanding learning probability and this game can be used as part of a classroom learning activity to help students improve their probability knowledge and problem-solving abilities.